Sacraments in the Scholastica Colonialis according to José de Acosta - Schmitt, Flávio (2012)
The image of the colonization of America that predominates in most discourses and analyses stresses the negative side of this process. The emphasis on this negative side is due to the role played Europeans, especially the role played by the Church. While, on the one hand, there are negative elements to be pointed out in the way the colonization took place, on the other, there are also examples and witnesses of persons belonging to the same Church accused of connivance and complicity who raised their voice to denounce the atrocities and defended the victims. The article discusses the contribution of José de Acosta in the analysis of the colonization of the Inca Empire and the role played by the Church in the missionary activity of the Jesuits. It particularly deals with Acosta's remarks on the sacraments, specifically on baptism and the Eucharist. In this way, the text highlights Acosta's contribution to the Scholastica Colonialis.